Surgical Resection of Native Viscera to Manage Persistent Ascites after Multivisceral Transplant - Brian I. Shaw; Andrew S. Barbas; Debra L. Sudan (Case Reports in Transplantation)
Multivisceral transplantation is the therapy of choice in patients with diffuse portomesenteric thrombosis. In the present case, we describe a patient who had persistent ascites after multivisceral transplant. The patient was initially diagnosed with a chyle leak which was cured via embolization. When this did not cure her ascites, reexploration proved the etiology to be at least partially attributable to persistent hypertension in the retained viscera. This was cured with the resection of her native viscera. This case highlights the importance of resection of all congested viscera at the time of transplantation in patients with diffuse portomesenteric thrombosis, the utility of preoperative embolization techniques in assisting this, and also the ability to perform delayed resection if necessary.